Water alkaline phosphatase activity andphosphorus availability during summer ininland water bodies - Manna, S K; Som, A B; Samanta, S (Indian Journal of Fisheries, 2011)
Phosphorus is a limiting nutrient in most freshwater environments. Alkalinephosphatase enzyme plays an important role in phosphorus cycling and may bedecisive in primary and secondary production. In the present investigation totalwater alkaline phosphatase activity was high during summer in all the waterbodies. Relative contributions of algal, bacterial and dissolved fractions to totalwater phosphatase activity were 11-50, 3-8 and 41-83% respectively. Unlike cellfree and bacterial phosphatases, phytoplankton specific enzyme activity waspositively correlated to orthophosphate concentration. Algal specific enzymeactivity was low suggesting P-uptake to be a more important process than Pregeneration in hyper-eutrophic sewage fed ponds.